Balmer breaks in simulated galaxies at z > 6 - Binggeli, Christian; Ceverino, Daniel (Monthly notices of the Royal Astronomical Society, 2019)
ABSTRACT. Photometric observations of the spectroscopically confirmed z ≈ 9.1 galaxy MACS1149-JD1 have indicated the presence of a prominent Balmer break in it